Why the League of Nations in 1920 did not challenge the title of the Republic of Armenia in Eastern Armenia and did not recognize the territorial claims of the Azerbaijan Democratic Republic as legitimate - Manasyan, Alexandr (Bulletin of Yerevan University C: Jurisprudence, 2024)
The article substantiates the thesis that none of the republics that appeared in the 20th century in Transcaucasia under the name Azerbaijan were established by an act of self-determination and did not have legally established borders. The first of them - the Azerbaijan Democratic Republic (ADR) - was created in 1918 by Ottoman troops invading Transcaucasia. The League of Nations refused the ADR's request to join its ranks, recognizing its territorial claims as unfounded either historically or demographically and noting the impossibility of defining its territories (and therefore its borders). It turned out that the formula “consisting of Eastern and Southern Transcaucasia” of the Declaration of Independence of the ADR, which formed the basis of its territorial claims, could not be verified. As far as the Republic of Armenia (RA) is concerned, the League did not challenge its title in the ethnically Armenian territories of the Russian Empire including Artsakh and marked the future territories of the RA after the entry into force of the Woodrow Wilson arbitration award. The ADR left history without recognized territories and borders when the XI Red Army of Soviet Russia entered Baku on April 28, abolished the ADR and proclaimed the Azerbaijan Soviet Socialist Republic (Az.SSR). The determination of the borders of the Transcaucasian Soviet republics was left to the government of Soviet Russia, which had entered into an agreement with Kemalist Turkey. In 1921, Nakhichevan and Nagorno-Karabakh (Artsakh), already recognized as territories of Soviet Armenia (Armenian SSR), were separated from the Armenian SSR and included within the borders of the Az. SSR. Nakhichevan - according to the Treaty of Kars (1921) with the status of a protected territory, and Artsakh - according to the “decision” of the Caucasian Bureau of the Russian Communist (Bolshevik) Party (Caucasian Bureau of the RCP/b/) with the status of national autonomy with broad rights (July 5, 1921). This “decision” is known not only because it came from a third party body that did not have the right to resolve territorial issues, but also because it was not actually adopted. Stalin read the text and, without putting it up for discussion and voting, closed the meeting of the Caucasian Bureau. During the collapse of the USSR, Baku declared its refusal to inherit Az. SSR, recognizing it as an illegal entity that emerged as a result of the annexation of Azerbaijan. Baku understood the absurdity of recognizing the legal borders of Az. SSR, which they considered an illegal entity. Therefore, they decided to remain faithful to  the heritage of the ADR in this matter. The formula for its territorial claims, rejected by the League of Nations, was in the way: “consisting of Eastern and Southern Transcaucasia”, the inconsistency of which was obvious. In the Constitutional Act “On State Independence of the Azerbaijan Republic” (October 18, 1991), Baku replaced it with another, but legally more meaningless: “The territory of the Azerbaijan Republic within the historically established borders is united, indivisible, inalienable” (Newspaper “Baku Worker”, November 7 1991), fundamentally not amenable to either delimitation or demarcation. With such “territories” and “borders” the Republic of Azerbaijan (AR) came to Almaty on December 21 to join the CIS and agree to the demands of the European Community put forward on December 16, 1991 in the “Statement of the Twelve” as criteria for the recognition of new states of Eastern Europe and the post-Soviet space. Europe turned a blind eye to the fact that Azerbaijan does not satisfy any of the criteria it put forward and apparently advised Baku to hold a referendum on independence in order to at least determine the borders with such an act. This first referendum on independence in the history of entities called “Azerbaijan” took place on December 29, 1991. But the question submitted to the referendum “Do you support the Constitutional Act adopted by the Supreme Council of the Republic of Azerbaijan “On State Independence?” left in force the thesis about historically established borders, devoid of legal meaning. The borders of the AR remained undefined. Realizing the absurdity of the situation, Baku removed the Constitutional Act from circulation, placed it on the presidential website, removing the words “within historically established boundaries” from the text.
Keywords: Caucasian Tatars; Republic of Armenia; Azerbaijan Democratic Republic; League of Nations; Republic of Azerbaijan; Republic of Artsakh; Statement of the “Twelve”